Work in Progress: Building a Virtual Reality Environment for Training UAV Pilots - Jaklic, Ales (IEEE Global Engineering Education Conference, 2025)
We present the design of a courseware program created for a university outreach summer school, aimed at promoting STEM education among upper K-12 students. This course addresses a real-world challenge: learning to fly a radiocontrolled Unmanned Aerial Vehicle (UAV), which can be both difficult and costly due to the high likelihood of crashes during training. To mitigate this issue, the program focuses on developing a virtual reality (VR) environment that allows students to train as UAV pilots in a safe, crash-free setting, reducing risks and costs associated with real-world practice.